Quantitative fetal fibronectin testing in combination with cervical length measurement in the prediction of spontaneous preterm delivery in symptomatic women. (15th December 2015) - Bruijn, MMC; Vis, JY; Wilms, FF; Oudijk, MA; Kwee, A; Porath, MM; Oei, G; Scheepers, HCJ; Spaanderman, MEA; Bloemenkamp, KWM; Haak, MC; Bolte, AC; et al.
Abstract : Objective: To evaluate whether in symptomatic women, the combination of quantitative fetal fibronectin (fFN) testing and cervical length (CL) improves the prediction of preterm delivery (PTD) within 7 days compared with qualitative fFN and CL. Design: Post hoc analysis of frozen fFN samples of a nationwide cohort study. Setting: Ten perinatal centres in the Netherlands. Population: Symptomatic women between 24 and 34 weeks of gestation. Methods: The risk of PTD <7 days was estimated in predefined CL and fFN strata. We used logistic regression to develop a model including quantitative fFN and CL, and one including qualitative fFN (threshold 50 ng/ml) and CL. We compared the models' capacity to identify women at low risk (<5%) for delivery within 7 days using a reclassification table. Main outcome measures: Spontaneous delivery within 7 days after study entry. Results: We studied 350 women, of whom 69 (20%) delivered within 7 days. The risk of PTD in <7 days ranged from 2% in the lowest fFN group (<10 ng/ml) to 71% in the highest group (>500 ng/ml). Multivariable logistic regression showed an increasing risk of PTD in <7 days with rising fFN concentration [10–49 ng/ml: odds ratio (OR) 1.3, 95% confidence interval (95% CI) 0.23–7.0; 50–199 ng/ml: OR 3.2, 95% CI 0.79–13; 200–499 ng/ml: OR 9.0, 95% CI 2.3–35; >500 ng/ml: OR 39, 95% CI 9.4–164] and shortening of the CL (OR 0.86 per mm, 95% CI 0.82–0.90). Use of quantitative fFN instead of qualitative fFN resulted in reclassification of 18 (5%) women from high to low risk, of whom one (6%) woman delivered within 7 days. Conclusion: In symptomatic women, quantitative fFN testing does not improve the prediction of PTD within 7 days compared with qualitative fFN testing in combination with CL measurement in terms of reclassification from high to low (<5%) risk, but it adds value across the risk range. Tweetable abstract: Quantitative fFN testing adds value to qualitative fFN testing with CL measurement in the prediction of PTD. Tweetable abstract: Quantitative fFN testing adds value to qualitative fFN testing with CL measurement in the prediction of PTD.